Assessment of Organ Dysfunction and Underlying Causes in Maternal Near-miss Cases at Health Care Facilities in Doiwala Block of District Dehradun – A Retrospective Study - Kanwar, Dhanak; Chaturvedi, Jaya; Singh, Mahendra; Aggarwal, Pradeep; Sharma, Nandita; Sadiq, Sabiha (Current Hypertension Reviews, 2023)
Introduction: The extent of maternal morbidity is a good gauge of a nation's maternal health care system. Maternal near-miss (MNM) cases need to be reviewed because they can indirectly contribute significantly to reducing the maternal mortality ratio in India. MNM cases can provide useful information in this context. Such women who survive these life-threatening conditions arising from complications during pregnancy, childbirth and post partum (42 days) share many commonalities with those who die because of such complications.Aim: To assess the organ dysfunction and the underlying causes, associated/contributory factors associated with
Keywords: COVID-19 pandemic